Cross-sectional observational study on correlation of obesity and overweight in children with insulin resistance based on HOMA-IR score - Clara Rilna Joseph; Harish Kumar; Kavitha Bhat (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2023)
With improvements in lifestyle and healthcare throughout the world, there has been an increasing incidence of obesity among adults and children. It is important that obesity and its adverse effects be recognized in childhood and measures be taken right from childhood to tackle the long-term outcomes of the same. We have studied the correlation of scores like Homeostasis Model Assessment-Insulin Resistance (HOMA-IR) and its relation with Insulin resistance in children. Which helps as a tool in early recognition of lifestyle diseases in children. It was seen that of a total of 50 children of which 40 children were obese (BMI greater than 95th centile) and 10 children were overweight (BMI greater than 85th centile), 43 children had insulin resistance based on HOMA-IR score (cut-off=2.5) and 7 were non-insulin resistant. From our study, it has been concluded that HOMA-IR has a strong correlation with BMI and can be used as a surrogate marker of Insulin resistance.